Black female head start teachers' multimodal meaning-making in prekindergarten read-alouds (Chicago The University of Chicago Press)
Young children draw from verbal and nonverbal input to make meaning from texts, a skill that is foundational for later reading comprehension and academic achievement. However, prior studies have focused solely on teachers' verbal input during prekindergarten read-a-louds. We examine four Black, female prekindergarten teachers' multimodal enactments of a text to identify how they socialize and orient children into language-building and meaning-making practices. Findings from our microethnographic analysis reveal four multimodal orientations: transmissive/ limited gesture, multimodal collaborative, multimodal de-scriber, and multimodal performance-oriented. Variations in teachers' inclusion of multiple modalities and child engagement indicate a constellation of multimodal read-aloud orientations and socialization practices along a spectrum of support. Teachers gestured to encourage engagement, index novel words, expand children's utterances, include culturally affirming discourse styles, and bridge the text into the classroom. We address how teachers express and represent meaning through language, im-ages, and gesture, as well as instructional implications of multimodal enactments.
Keywords: Elementary